2016
DOI: 10.1080/16864360.2016.1150720
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge integration in CAD-CAM process chain

Abstract: The automatic detection of engineering drawing modifications made by other designers is central to improving CAD/CAPP working efficiency levels. Engineering drawings include numerous entities, but only a few entities are modified. It is difficult for designers to identify modified entities in a complex drawing. This paper presents a novel means of detecting entities in engineering drawings created by other designers that employs semi-fragile watermark technologies. Modifications will change embedded watermarks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Depending on the requirements, a configurator places the UDFs in the CAD assembly. Moreover Manoharan et al (2016) shows knowledge integration in the CAD-CAM process chain through the example of NC and additive manufacturing. Here, the author implements a web service for linking the CAD system with the respective databases (Figure 1).…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the requirements, a configurator places the UDFs in the CAD assembly. Moreover Manoharan et al (2016) shows knowledge integration in the CAD-CAM process chain through the example of NC and additive manufacturing. Here, the author implements a web service for linking the CAD system with the respective databases (Figure 1).…”
Section: State Of the Artmentioning
confidence: 99%
“…Here, the author implements a web service for linking the CAD system with the respective databases (Figure 1). According to Manoharan et al (2016), one important advantage for using a web service is if changes are needed in the database structure. This ensures that only the web service or the database has to be adapted and not the expert system.…”
Section: State Of the Artmentioning
confidence: 99%
“…the process of capturing and formalizing expertise before its implementation in an IT system. Manoharan et al (2016) have instead shown how a manufacturing knowledge integration in CAD systems can support the planning and work preparation.…”
Section: Introductionmentioning
confidence: 99%